Redistributive Agriculture land reforms in Bangladesh: an inquiry into constraints - Reza-E-Rabbi, Mohammad (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2009.